High voltage insulating ceramic material for high energy ray tubes and method for producing the same
Patent Information
- Application Number
- CN202611244852.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]为了解决高压绝缘陶瓷材料无法在保持初始绝缘性能的前提下、对服役过程中产生的微裂纹进行原位多次自修复的问题,本申请提供了一种用于高能射线管的高压绝缘陶瓷材料,所述陶瓷材料包括氧化铝陶瓷基体、微胶囊和导电触发纳米颗粒,所述氧化铝陶瓷基体中氧化铝的质量分数为96%~99%;所述微胶囊分散于所述氧化铝陶瓷基体的晶界处,所述微胶囊为壳核结构,核层材料为软化温度500℃~750℃的低熔点玻璃,所述低熔点玻璃在800℃以下的体积电阻率≥1×108Ω·cm、室温体积电阻率≥1×1012Ω·cm;所述导电触发纳米颗粒附着于微胶囊表面或弥散分布于晶界,用于在裂纹尖端形成局域导电通道,产生焦耳热以触发微胶囊修复,以所述氧化铝陶瓷基体的质量分数为100%计,导电触发纳米颗粒的质量分数为0.2%~1.5%
[0017] This application provides a high-voltage insulating ceramic material for high-energy X-ray tubes, solving the problem that high-voltage insulating ceramic materials cannot perform in-situ multiple self-repairs of microcracks generated during service while maintaining initial insulation performance. This application also provides a method for preparing the above-mentioned ceramic material.
Smart Images

Figure CN122916627A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-voltage insulating ceramic materials technology, and in particular to a high-voltage insulating ceramic material for high-energy X-ray tubes and its preparation method. Background Technology
[0002] As industrial non-destructive testing demands increasingly higher penetration capabilities, X-ray tubes are expanding from the traditional 150kV~200kV to 300kV, 350kV, and even higher voltage levels. This also places higher demands on the electrical insulation performance of their core component, the high-voltage insulating ceramic shell. Currently, the industry mainly uses high-purity alumina ceramic as the matrix material. By optimizing the formula, adding toughening phases, controlling grain size, and improving the sintering process, efforts are being made to obtain ceramic products with high density and high insulation strength to meet the basic voltage withstand and reliability requirements of X-ray tubes.
[0003] With increasing operating voltage, even high-density alumina ceramics are highly susceptible to microcracks due to partial discharge and electrical treeing under the combined effects of long-term strong electric fields, thermal cycling, and mechanical stress. Once these microcracks form, they become weak points in the insulation, gradually lowering the breakdown threshold and ultimately leading to insulation failure. Passive protection strategies such as toughening or structural optimization have been attempted to address this issue, but these methods can only delay crack formation and cannot effectively repair existing micro-damage. Furthermore, self-healing ceramic solutions that have emerged in recent years either contain conductive phases in their repair agents, resulting in non-insulating products after repair, or rely on a high-temperature environment for triggering, making them unsuitable for responding to the instantaneous heat release in micro-regions under X-ray tube operating conditions. In addition, the mismatch in thermal expansion coefficients between the repair material and the alumina matrix further complicates matters, making it impossible to achieve in-situ, efficient repair of microcracks while meeting high-voltage insulation requirements.
[0004] To address the problem that high-voltage insulating ceramic materials cannot perform in-situ multiple self-repairs of microcracks generated during service while maintaining their initial insulation performance, this application provides a high-voltage insulating ceramic material for high-energy X-ray tubes and its preparation method. Summary of the Invention
[0005] To address the issue that high-voltage insulating ceramic materials cannot perform in-situ, repeated self-repair of microcracks generated during service while maintaining initial insulation performance, this application provides a high-voltage insulating ceramic material for high-energy X-ray tubes. The ceramic material comprises an alumina ceramic matrix, microcapsules, and conductive triggering nanoparticles. The alumina ceramic matrix contains 96%–99% alumina by mass. The microcapsules are dispersed at the grain boundaries of the alumina ceramic matrix, and each microcapsule has a core-shell structure. The core layer material is a low-melting-point glass with a softening temperature of 500℃–750℃, and the volume resistivity of the low-melting-point glass below 800℃ is ≥1×10⁻⁶. 8Ω·cm, room temperature volume resistivity ≥1×10 12 Ω·cm; The conductive triggering nanoparticles are attached to the surface of the microcapsule or dispersed at the grain boundaries to form a local conductive channel at the crack tip, generating Joule heat to trigger microcapsule repair. The mass fraction of the conductive triggering nanoparticles is 0.2%~1.5% based on the mass fraction of the alumina ceramic matrix as 100%.
[0006] In this application, the alumina ceramic matrix serves as the main structural material for high-voltage insulation, providing fundamental mechanical strength, bulk density, and insulation strength. Microcapsules are dispersed at the grain boundaries of the alumina ceramic matrix, each microcapsule being an independent core-shell structural unit. The shell material is a high-temperature resistant inert ceramic, such as Al₂O₃, ZrO₂, or SiO₂, maintaining structural integrity during the high-temperature sintering process and isolating the low-melting-point glass core layer from the external environment, preventing premature outflow and reaction with the matrix during sintering. The core layer material is a low-melting-point glass with a softening temperature of 500℃~750℃, and its volume resistivity below 800℃ is ≥1×10⁻⁶. 8 The volume resistivity at room temperature is ≥1×10¹² Ω·cm, ensuring that the repaired glass body possesses high insulation properties. Conductive triggering nanoparticles are attached to the surface of microcapsules or dispersed at grain boundaries. Their function is as follows: When microcracks are generated in the ceramic matrix due to partial discharge and electric treeing, the crack tip is often accompanied by strong local electric field concentration and micro-discharge phenomena. The conductive triggering nanoparticles form local conductive channels at the crack tip. When the micro-discharge current flows through the conductive channel, it generates Joule heating, causing the temperature of the micro-region around the crack to rise rapidly above the softening point of the core glass, triggering the microcapsule to rupture and release molten glass. Under the action of capillary force, the molten glass quickly fills along the microcrack, and after cooling, it forms a dense, high-resistivity glass body, "welding" the crack and restoring its insulation properties.
[0007] First, under normal service conditions, the microcapsule shell remains intact, and the conductive triggering nanoparticles are dispersed as isolated particles, without forming a continuous conductive network, thus not reducing the initial insulation strength of the ceramic material. Second, when microcracks occur, the Joule heating associated with the crack tip itself serves as a trigger signal, achieving in-situ self-repair through "damage-triggered" action, without relying on a high-temperature environment, resulting in a fast and precise response. Third, the amount of conductive triggering nanoparticles added is controlled within the range of 0.2% to 1.5%, ensuring that an effective local conductive channel is formed at the crack tip to generate sufficient Joule heating, while avoiding the formation of a conductive network due to excessive addition, which would damage the insulation performance. Finally, the volume resistivity of the core layer low-melting-point glass below 800℃ is ≥1×10⁻⁶. 8With a volume resistivity of ≥1×10¹² Ω·cm at room temperature, the repaired glassy body possesses high resistivity and exhibits excellent thermal expansion coefficient matching with the alumina matrix, making it less prone to secondary cracking upon cooling. The repaired area maintains reliable insulation performance over a long period. Furthermore, each microcapsule operates independently; a single repair consumes only a small number of microcapsules in the cracked area, leaving other unbroken microcapsules intact. Therefore, when new microcracks develop, the repair process can be repeated, achieving multiple self-repair capabilities. In summary, this application, through the synergistic effect of the alumina matrix, core-shell structured microcapsules, and conductive triggering nanoparticles, enables high-voltage insulating ceramic materials to maintain excellent initial insulation performance while possessing in-situ, multiple-time self-repair capabilities against microcracks.
[0008] Optionally, based on a mass fraction of 100% for the low-melting-point glass, the low-melting-point glass comprises 30%~40% SiO2, 15%~25% B2O3, 12%~20% BaO, 5%~10% Al2O3, 5%~10% ZnO, and 3%~8% CaO, with the sum of the mass percentages of each component being 100%.
[0009] Optionally, the shell material of the microcapsule is one or more of Al2O3, ZrO2, and SiO2, and the thickness of the shell is 0.2μm to 1μm.
[0010] Optionally, the average particle size of the microcapsules is 2μm~12μm, and the mass ratio of the core material to the shell material is (6~12):1.
[0011] Optionally, the particle size of the conductive triggering nanoparticles is 20nm~150nm, and the conductive triggering nanoparticles are one or more of SiC, TiN, and aluminum-doped zinc oxide (ZnO:Al).
[0012] Optionally, the alumina ceramic matrix has an average grain size of 3μm~8μm and a bulk density ≥3.68g / cm³. 3 Insulation strength ≥45kV / mm.
[0013] This application also provides a method for preparing ceramic materials, specifically including: S1 Preparation of microcapsules: Low melting point glass raw materials are mixed, melted, water-quenched, and ball-milled to obtain low melting point glass powder; the glass powder and shell material precursor are spray-dried or fluidized bed coated to obtain core-shell wet particles, and the shell is densified by heat treatment at 700℃~850℃ to obtain microcapsules. S2 Powder Mixing: The microcapsules, alumina powder, conductive triggering nanoparticles and sintering aid are wet ball-milled and mixed for 12-24 hours, dried and sieved to obtain mixed powder. S3 molding: The mixed powder is dry-pressed into shape, and then subjected to cold isostatic pressing to obtain a ceramic green body; S4 High-temperature sintering: The green body is placed in air or a humid hydrogen atmosphere and sintered at 1450℃~1620℃ for 2~4 hours, with segmented heating rate controlled throughout the sintering process. S5 Post-processing: The sintered ceramic blank is subjected to surface grinding, polishing, cleaning and drying to obtain the finished high-voltage insulating ceramic material.
[0014] Optionally, the melting temperature of the low-melting-point glass powder in S1 is 1200℃~1350℃, and the average particle size of the low-melting-point glass powder after ball milling is 1μm~4μm; the shell material precursor is one of aluminum sol, zirconium sol or silica sol, with a solid content of 10%~25%.
[0015] Optionally, the sintering aid mentioned in S2 is one or more of MgO, TiO2, CaO, Y2O3, and Cr2O3, and the amount of sintering aid added is 0.25% to 2.5% of the mass of alumina powder.
[0016] Optionally, the segmented heating rate control throughout the sintering process described in S4 specifically includes: heating from room temperature to 600℃ at a rate of 1℃~2℃ / min, holding for 1~2 hours to remove the binder; heating from 600℃ to 1200℃ at a rate of 5℃~10℃ / min; heating from 1200℃ to the sintering temperature at a rate of 2℃~5℃ / min; and cooling to room temperature at a rate of 3℃~5℃ / min after holding.
[0017] This application provides a high-voltage insulating ceramic material for high-energy X-ray tubes, solving the problem that high-voltage insulating ceramic materials cannot perform in-situ multiple self-repairs of microcracks generated during service while maintaining initial insulation performance. This application also provides a method for preparing the above-mentioned ceramic material. Attached Figure Description
[0018] To more clearly illustrate the technical solution of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a flowchart of a method for preparing high-voltage insulating ceramic materials for high-energy X-ray tubes. Detailed Implementation
[0020] The embodiments will now be described in detail. The implementations described in the following embodiments are merely examples of systems and methods consistent with some aspects of the invention as detailed in the claims.
[0021] To address the issue that high-voltage insulating ceramic materials cannot perform in-situ, repeated self-repair of microcracks generated during service while maintaining initial insulation performance, this application provides a high-voltage insulating ceramic material for high-energy X-ray tubes. The ceramic material comprises an alumina ceramic matrix, microcapsules, and conductive triggering nanoparticles. The alumina ceramic matrix contains 96%–99% alumina by mass. The microcapsules are dispersed at the grain boundaries of the alumina ceramic matrix, and each microcapsule has a core-shell structure. The core layer material is a low-melting-point glass with a softening temperature of 500℃–750℃, and the volume resistivity of the low-melting-point glass below 800℃ is ≥1×10⁻⁶. 8 Ω·cm, room temperature volume resistivity ≥1×10 12 Ω·cm; The conductive triggering nanoparticles are attached to the surface of the microcapsule or dispersed at the grain boundaries to form a local conductive channel at the crack tip, generating Joule heat to trigger microcapsule repair. The mass fraction of the conductive triggering nanoparticles is 0.2%~1.5% based on the mass fraction of the alumina ceramic matrix as 100%.
[0022] In this application, the alumina ceramic matrix serves as the main structural material for high-voltage insulation, providing fundamental mechanical strength, bulk density, and insulation strength. Microcapsules are dispersed at the grain boundaries of the alumina ceramic matrix, each microcapsule being an independent core-shell structural unit. The shell material is a high-temperature resistant inert ceramic, such as Al2O3, ZrO2, or SiO2, which maintains structural integrity during the high-temperature sintering process, isolating the low-melting-point glass core layer from the external environment and preventing it from prematurely flowing out and reacting with the matrix during sintering. The core layer material is a low-melting-point glass with a softening temperature of 500℃~750℃, and its volume resistivity below 800℃ is ≥1×10⁻⁶. 8 The volume resistivity at room temperature is ≥1×10¹² Ω·cm, ensuring that the repaired glass body possesses high insulation properties. Conductive triggering nanoparticles are attached to the surface of microcapsules or dispersed at grain boundaries. Their function is as follows: When microcracks are generated in the ceramic matrix due to partial discharge and electric treeing, the crack tip is often accompanied by strong local electric field concentration and micro-discharge phenomena. The conductive triggering nanoparticles form local conductive channels at the crack tip. When the micro-discharge current flows through the conductive channel, it generates Joule heating, causing the temperature of the micro-region around the crack to rise rapidly above the softening point of the core glass, triggering the microcapsule to rupture and release molten glass. Under the action of capillary force, the molten glass quickly fills along the microcrack, and after cooling, it forms a dense, high-resistivity glass body, "welding" the crack and restoring its insulation properties.
[0023] In some embodiments, the low-melting-point glass comprises 30%~40% SiO2, 15%~25% B2O3, 12%~20% BaO, 5%~10% Al2O3, 5%~10% ZnO and 3%~8% CaO, with the sum of the mass percentages of each component being 100%.
[0024] In some embodiments, the shell material of the microcapsule is one or more of Al2O3, ZrO2, and SiO2, and the thickness of the shell is 0.2 μm to 1 μm.
[0025] In some embodiments, the average particle size of the microcapsules is 2 μm to 12 μm, and the mass ratio of the core material to the shell material is (6 to 12):1.
[0026] In some embodiments, the particle size of the conductive triggering nanoparticles is 20 nm to 150 nm, and the conductive triggering nanoparticles are one or more of SiC, TiN, and aluminum-doped zinc oxide.
[0027] In some embodiments, the alumina ceramic matrix has an average grain size of 3 μm to 8 μm and a bulk density ≥ 3.68 g / cm³. 3 Insulation strength ≥45kV / mm.
[0028] This application also provides a method for preparing ceramic materials, specifically comprising: S1 Preparation of microcapsules: Low melting point glass raw materials are mixed, melted, water-quenched, and ball-milled to obtain low melting point glass powder; the glass powder and shell material precursor are spray-dried or fluidized bed coated to obtain core-shell wet particles, and the shell is densified by heat treatment at 700℃~850℃ to obtain microcapsules. S2 Powder Mixing: The microcapsules, alumina powder, conductive triggering nanoparticles and sintering aid are wet ball-milled and mixed for 12-24 hours, dried and sieved to obtain mixed powder. S3 molding: The mixed powder is dry-pressed into shape, and then subjected to cold isostatic pressing to obtain a ceramic green body; S4 High-temperature sintering: The green body is placed in air or a humid hydrogen atmosphere and sintered at 1450℃~1620℃ for 2~4 hours, with segmented heating rate controlled throughout the sintering process. S5 Post-processing: The sintered ceramic blank is subjected to surface grinding, polishing, cleaning and drying to obtain the finished high-voltage insulating ceramic material.
[0029] In some embodiments, the alumina ceramic matrix is obtained by sintering and densifying high-purity alumina powder, and the sintered alumina powder forms a complete and continuous insulating skeleton.
[0030] In some embodiments, the melting temperature of the low melting point glass powder in S1 is 1200℃~1350℃, and the average particle size of the low melting point glass powder after ball milling is 1μm~4μm; the shell material precursor is one of aluminum sol, zirconium sol or silica sol, with a solid content of 10%~25%.
[0031] In some embodiments, the sintering aid mentioned in S2 is one or more of MgO, TiO2, CaO, Y2O3, and Cr2O3, and the amount of sintering aid added is 0.25% to 2.5% of the mass of alumina powder.
[0032] In some embodiments, the segmented heating rate control throughout the sintering process described in S4 specifically includes: heating from room temperature to 600°C at a heating rate of 1°C~2°C / min, holding for 1~2 hours to remove the binder; heating from 600°C to 1200°C at a heating rate of 5°C~10°C / min; heating from 1200°C to the sintering temperature at a heating rate of 2°C~5°C / min; and cooling to room temperature at a rate of 3°C~5°C / min after holding.
[0033] In some embodiments, the method for preparing the ceramic material provided in this application includes the following steps: Step 1: Weigh the low-melting-point glass raw materials according to the formula, mix them evenly, and melt them at 1200℃~1350℃ for 1~2 hours. Then, water quench, ball mill, and sieve to obtain glass powder core material with an average particle size of 1μm~4μm. Mix the core material with the shell material precursor (aluminum sol, zirconium sol, or silica sol, solid content 10%~25%) in a certain proportion, and coat it through spray drying (inlet temperature 180℃~220℃, outlet temperature 90℃~110℃) or fluidized bed coating to form core-shell structured wet particles. Then, heat treat at 700℃~850℃ for 1~3 hours to densify the shell material, obtaining repair-functional microcapsules.
[0034] Step 2: Take 100 parts of alumina powder with a purity of 96%~99%, 3~12 parts of repair-functional microcapsules, 0.2~1.5 parts of conductive triggering nanoparticles, and 0.25~2.5 parts of one or more of MgO, TiO2, CaO, Y2O3, and Cr2O3 as sintering aids. Add the above powders to a planetary ball mill, add anhydrous ethanol or deionized water as the medium, with a material:ball:water ratio of 1:2:0.6~0.8, and ball mill for 12~24 hours at a speed of 150~250 r / min. After ball milling, dry the slurry at 80℃~120℃ and pass it through an 80-200 mesh sieve.
[0035] Step 3: Perform dry pressing, setting the pressure to 20~50MPa. After dry pressing, the mixed powder is then subjected to cold isostatic pressing, setting the isostatic pressing pressure to 100~200MPa to obtain a green body. The green body density should reach 55%~65% of the theoretical density.
[0036] Step 4: Place the green body in a high-temperature furnace and sinter it in air or a humid hydrogen atmosphere. The heating program is as follows: from room temperature to 600℃, heating rate 1℃~2℃ / min, hold at 600℃ for 1~2 hours for debinding; from 600℃ to 1200℃, heating rate 5℃~10℃ / min; from 1200℃ to the sintering temperature of 1450℃~1620℃, heating rate 2℃~5℃ / min; hold for 2~4 hours; cool with the furnace at a cooling rate of 3℃~5℃ / min.
[0037] Step 5: Grind and polish the sintered ceramic surface until the inner surface roughness is ≤1μm.
[0038] Example 1: Step 1: Weigh the glass raw materials according to the following mass percentages: SiO2 32%, B2O3 22%, BaO 16%, Al2O3 10%, ZnO 12%, CaO 8%, total 100%. Mix the raw materials evenly and place them in a crucible. Melt at 1300℃ for 1.5 hours. Pour the molten glass into deionized water for water quenching to obtain glass fragments. After ball milling, drying, and sieving, obtain low-melting-point glass powder with an average particle size of 2.5μm.
[0039] Take 100g of the above glass powder and mix it with 200mL of aluminum sol with a solid content of 20% and an average particle size of 50nm. After mixing evenly, granulate it through a spray dryer. Set the inlet temperature of the spray granulator to 200℃ and the outlet temperature to 100℃. Heat treat the resulting core-shell structured wet particles in an air atmosphere at 800℃ for 2h to densify the Al2O3 shell material, and obtain repair function microcapsules with an average particle size of 8μm, a shell thickness of about 0.6μm, and a core material to shell material mass ratio of about 8:1.
[0040] Step 2: Take 1000g of alumina powder with a purity ≥96% and an average particle size of 1.2μm, 60g of the microcapsules prepared in Step 1, 8g of SiC powder with an average particle size of 80nm as conductive triggering nanoparticles, and 2.5g of MgO, 10g of TiO2, and 3g of Y2O3 as sintering aids. Mix and ball-mill the above powders for 12 hours, dry, and sieve to obtain a mixed powder.
[0041] Step 3: The mixed powder is dry-pressed at 40MPa and then subjected to cold isostatic pressing at 150MPa for 5 minutes to obtain the green body.
[0042] Step 4: Place the green body in a high-temperature muffle furnace and sinter in air atmosphere. The heating program is set as follows: from room temperature to 600℃, heating rate 1.5℃ / min, hold at 600℃ for 1.5h for debinding; from 600℃ to 1200℃, heating rate 8℃ / min; from 1200℃ to 1580℃, heating rate 3℃ / min; hold at 1580℃ for 3h; then cool to room temperature at 4℃ / min.
[0043] Step 5: Grind and polish the surface of the sintered ceramic sheet to make the surface roughness Ra≤0.6μm, then ultrasonically clean and dry.
[0044] The ceramic material prepared in Example 1 has a bulk density of 3.71 g / cm³. 3 The average grain size is 5.2 μm, and the initial insulation strength is 46.2 kV / mm. Accelerated electrical aging tests were conducted at 300 kV (the rated voltage being the test voltage, 300 kV). The partial discharge initiation voltage was 300 kV × 85% = 255 kV. After 50 hours of continuous aging, the insulation strength decreased to 31.5 kV / mm. The sample was then kept in a 120℃ oven for 2 hours, cooled to room temperature, and tested again; the insulation strength recovered to 43.8 kV / mm. Repeating the aging and repair cycle, the insulation strength after the second repair was 41.5 kV / mm, and after the third repair it was 39.29 kV / mm, still maintaining more than 85% of the initial value. This indicates that the material possesses at least two effective self-healing capabilities.
[0045] Example 2: Step 1: Weigh the glass raw materials according to the following mass percentages: SiO2 40%, B2O3 25%, BaO 20%, Al2O3 5%, ZnO 7%, CaO 3%, total 100%. Mix the raw materials evenly and place them in a crucible. Melt at 1300℃ for 1.5 hours. Pour the molten glass into deionized water for water quenching to obtain glass fragments. After ball milling, drying, and sieving, obtain low-melting-point glass powder with an average particle size of 4.0 μm.
[0046] Take 100g of the above glass powder and mix it with 200mL of aluminum sol with a solid content of 25% and an average particle size of 50nm. After mixing evenly, granulate it through a spray dryer. Set the inlet temperature of the spray granulator to 200℃ and the outlet temperature to 100℃. Heat treat the resulting core-shell structured wet particles in an air atmosphere at 850℃ for 2h to densify the Al2O3 shell material, and obtain repair function microcapsules with an average particle size of 2μm, a shell thickness of about 0.2μm, and a core material to shell material mass ratio of about 6:1.
[0047] Step 2: Take 1000g of alumina powder with a purity ≥96% and an average particle size of 8.0μm, 60g of the microcapsules obtained in Step 1, 15g of SiC powder with an average particle size of 150nm as conductive triggering nanoparticles, and 5g of MgO, 10g of TiO2, 5g of Y2O3, and 5g of CaO as sintering aids. Mix and ball-mill the above powders for 13 hours, dry, and sieve to obtain a mixed powder.
[0048] Step 3: The mixed powder is dry-pressed at 40MPa and then subjected to cold isostatic pressing at 150MPa for 5 minutes to obtain the green body.
[0049] Step 4: Place the green body in a high-temperature muffle furnace and sinter in air atmosphere. The heating program is set as follows: room temperature to 600℃, heating rate 1.5℃ / min, hold at 600℃ for 1.5h for debinding; 600℃ to 1200℃, heating rate 5℃ / min; 1200℃ to 1620℃, heating rate 5℃ / min; hold at 1620℃ for 2h; then cool to room temperature at 4℃ / min.
[0050] Step 5: Grind and polish the surface of the sintered ceramic sheet to make the surface roughness Ra≤0.6μm, then ultrasonically clean and dry.
[0051] The ceramic material prepared in Example 2 has a bulk density of 3.74 g / cm³. 3 The initial insulation strength was 47.8 kV / mm. After an accelerated electrical aging test at 300 kV (rated voltage 300 kV, partial discharge initiation voltage 255 kV) for 50 hours, the insulation strength decreased to 30.8 kV / mm. The sample was then kept in a 120℃ oven for 2 hours, cooled to room temperature, and tested again; the insulation strength recovered to 44.5 kV / mm. Repeating the aging and repair cycle, the insulation strength after the second repair was 40.1 kV / mm, and after the third repair it was 37.6 kV / mm, still maintaining above 80% of the initial insulation strength, demonstrating that the formulation system possesses stable, multiple-cycle in-situ self-repair capability.
[0052] Example 3: Step 1: Weigh the glass raw materials according to the following mass percentages: SiO2 40%, B2O3 15%, BaO 20%, Al2O3 9%, ZnO 9%, CaO 7%, total 100%. Mix the raw materials evenly and place them in a crucible. Melt at 1200℃ for 1.5 hours. Pour the molten glass into deionized water for quenching to obtain glass fragments. After ball milling, drying, and sieving, obtain low-melting-point glass powder with an average particle size of 1.0 μm.
[0053] Take 100g of the above glass powder and mix it with 200mL of aluminum sol with a solid content of 10% and an average particle size of 55nm. After mixing evenly, granulate it through a spray dryer. Set the inlet temperature of the spray granulator to 200℃ and the outlet temperature to 100℃. Heat treat the resulting core-shell structured wet particles in an air atmosphere at 800℃ for 2h to densify the Al2O3 shell material, and obtain repair function microcapsules with an average particle size of 12μm, a shell thickness of about 1.0μm, and a core material to shell material mass ratio of about 12:1.
[0054] Step 2: Take 1000g of alumina powder with a purity ≥96% and an average particle size of 3.0μm, 60g of the microcapsules prepared in Step 1, 2g of SiC powder with an average particle size of 20nm as conductive triggering nanoparticles, and 1.5g of MgO and 1g of TiO2 as sintering aids. Mix the above powders and ball mill for 24h, dry and sieve to obtain a mixed powder.
[0055] Step 3: The mixed powder is dry-pressed at 40MPa and then subjected to cold isostatic pressing at 150MPa for 5 minutes to obtain the green body.
[0056] Step 4: Place the green body in a high-temperature muffle furnace and sinter in air atmosphere. The heating program is set as follows: from room temperature to 600℃, heating rate 1.5℃ / min, hold at 600℃ for 1.5h for debinding; from 600℃ to 1200℃, heating rate 10℃ / min; from 1200℃ to 1450℃, heating rate 3℃ / min; hold at 1450℃ for 4h; then cool to room temperature at 5℃ / min.
[0057] Step 5: Grind and polish the surface of the sintered ceramic sheet to make the surface roughness Ra≤0.6μm, then ultrasonically clean and dry.
[0058] The ceramic material prepared in Example 3 has a bulk density of 3.72 g / cm³. 3 The initial insulation strength was 47.5 kV / mm. After 50 hours of electrical aging at 300 kV high voltage, the insulation strength dropped to 32.1 kV / mm; after repair treatment by heat preservation at 120℃ for 2 hours, the insulation strength was restored to 44.6 kV / mm.
[0059] Example 4: Step 1: Weigh the glass raw materials according to the following mass percentages: SiO2 38%, B2O3 22%, BaO 16%, Al2O3 8%, ZnO 8%, and CaO 8%, for a total of 100%. Mix the raw materials evenly and place them in a crucible. Melt the mixture at 1250℃ for 2 hours. Pour the molten glass into deionized water for quenching to obtain glass fragments. After drying and sieving, obtain low-melting-point glass powder with an average particle size of 2.0 μm.
[0060] Take 100g of the above glass powder and mix it evenly with 180mL of zirconium sol with a solid content of 15% and an average particle size of 30nm. Then, granulate it by fluidized bed coating. Set the coating temperature to 150℃, the fluidizing gas velocity to 0.5m / s, and the coating time to 30min. The resulting core-shell particles are heat-treated in air at 750℃ for 3h to densify the ZrO2 shell material, resulting in repair-functional microcapsules with an average particle size of 6μm, a shell thickness of about 0.5μm, and a core material to shell material mass ratio of about 9:1.
[0061] Step 2: Take 1000g of alumina powder with a purity ≥97% and an average particle size of 1.0μm, 80g of the microcapsules prepared in Step 1, 12g of TiN powder with an average particle size of 50nm as conductive triggering nanoparticles, and 3g of MgO and 5g of Cr2O3 as sintering aids. Mix and ball-mill the above powders for 12h, dry, and sieve to obtain a mixed powder.
[0062] Step 3: The mixed powder is dry-pressed at 50MPa pressure and then subjected to cold isostatic pressing at 180MPa to obtain a green body.
[0063] Step 4: Place the green blank in a high-temperature furnace and sinter under a moist hydrogen atmosphere. The heating program is set as follows: from room temperature to 600℃, heating rate 1℃ / min, hold at 600℃ for 2 hours; from 600℃ to 1200℃, heating rate 6℃ / min; from 1200℃ to 1600℃, heating rate 2.5℃ / min; hold at 1600℃ for 2.5 hours; cool to room temperature at 3.5℃ / min.
[0064] Step 5: Grind and polish the surface of the sintered ceramic sheet to make the surface roughness Ra≤0.6μm, then ultrasonically clean and dry.
[0065] The ceramic material prepared in Example 4 has a bulk density of 3.73 g / cm³. 3 The average grain size was 4.5 μm, and the initial insulation strength was 48.5 kV / mm. After electrical aging at 350 kV for 50 hours, the insulation strength decreased to 33.2 kV / mm. After the sample was kept in a 150℃ oven for 1.5 hours, cooled, and tested, the insulation strength recovered to 45.1 kV / mm. A second aging-repair process restored it to 43.2 kV / mm.
[0066] Example 5: Step 1: Weigh the glass raw materials according to the following mass percentages: SiO2 35%, B2O3 20%, BaO 15%, Al2O3 12%, ZnO 10%, CaO 8%, totaling 100%. Mix the raw materials evenly and melt them at 1350℃ for 1.5 hours. Pour the molten glass into deionized water for water quenching to obtain glass fragments. After drying and sieving, low-melting-point glass powder with an average particle size of 1.5 μm is obtained.
[0067] Take 100g of the above glass powder and mix it with 220mL of silica sol with a solid content of 22% and an average particle size of 20nm. Set the inlet temperature to 210℃ and the outlet temperature to 105℃ for spray drying and granulation. Then, heat treat it in air at 700℃ for 3h to densify the SiO2 shell material and obtain repair function microcapsules with an average particle size of 5μm, a shell thickness of about 0.4μm, and a core-shell mass ratio of about 10:1.
[0068] Step 2: Take 1000g of alumina powder with a purity ≥99% and an average particle size of 0.8μm, 50g of the microcapsules prepared in Step 1, and 6g of aluminum-doped zinc oxide (ZnO:Al) with an average particle size of 60nm as conductive triggering nanoparticles; take 2g of MgO, 4g of Y2O3, and 8g of TiO2 as sintering aids. Mix and ball-mill the above powders for 12h, dry, and sieve to obtain a mixed powder.
[0069] Step 3: The mixed powder is dry-pressed at 30MPa pressure and then subjected to cold isostatic pressing at 200MPa to obtain a green body.
[0070] Step 4: Sintering in an air atmosphere. The heating program is as follows: from room temperature to 600℃, 2℃ / min, hold at 600℃ for 1 hour; from 600℃ to 1200℃, 7℃ / min; from 1200℃ to 1650℃, 2℃ / min; hold at 1650℃ for 2 hours; cool to room temperature at 3℃ / min.
[0071] Step 5: Grind and polish the surface of the sintered ceramic sheet to make the surface roughness Ra≤0.6μm, then ultrasonically clean and dry.
[0072] The ceramic material prepared in Example 5 had a bulk density of 3.76 g / cm³, an average grain size of 3.8 μm, and an initial insulation strength of 48.3 kV / mm. After electrical aging at 350 kV for 50 hours, the insulation strength decreased to 36.5 kV / mm, but recovered to 45.1 kV / mm after being repaired by heat treatment at 120°C for 2 hours. After being assembled into a CT X-ray tube, it operated continuously for 2000 hours under rated conditions of 160 kV without any insulation breakdown fault.
[0073] Comparative Example 1: This comparative example uses the same 96% pure alumina matrix and sintering process as Example 1, but without adding any repair-functional microcapsules or conductive triggering nanoparticles. Specifically: 1000g of 96% alumina powder, 2.5g of MgO, 10g of TiO2, and 3g of Y2O3 as sintering aids were taken, and the above powders were mixed, ball-milled, dried, and sieved to obtain a mixed powder; the mixed powder was dry-pressed under 40MPa pressure, and then subjected to cold isostatic pressing at 150MPa for 5 minutes to obtain a green body; the green body was placed in a high-temperature muffle furnace and sintered in air atmosphere. The heating program was set as follows: from room temperature to 600℃, heating rate 1.5℃ / min, holding at 600℃ for 1.5h for debinding; from 600℃ to 1200℃, heating rate 8℃ / min; from 1200℃ to 1580℃, heating rate 3℃ / min; holding at 1580℃ for 3h; then cooling to room temperature at 4℃ / min; the surface of the sintered ceramic sheet was ground and polished to make the surface roughness Ra≤0.6μm, ultrasonically cleaned and dried.
[0074] The ceramic material prepared in Comparative Example 1 had a bulk density of 3.69 g / cm³. 3 The initial insulation strength was 44.8 kV / mm. After electrical aging at 300 kV for 50 hours, the insulation strength dropped to 28.2 kV / mm. After the sample was kept in a 120℃ oven for 2 hours and then cooled, the insulation strength did not recover and remained at 28.1 kV / mm. Upon further aging, it rapidly broke down. This indicates that traditional ceramics without self-healing components lack any self-healing ability; once microcracks form, they permanently fail.
[0075] Comparative Example 2: This comparative example uses the same formulation as Example 1, but the repair agent is added directly as uncoated low-melting-point glass powder, without preparing core-shell microcapsules. Specifically, low-melting-point glass powder with an average particle size of 2.5 μm is prepared according to step 1 of Example 1, but without shell coating and heat treatment. 1000 g of 96% alumina powder, 60 g of glass powder, 8 g of conductive triggering nanoparticles SiC, and 2.5 g of MgO, 10 g of TiO2, and 3 g of Y2O3 are taken directly as sintering aids. The above powders are mixed, ball-milled, dried, and sieved to obtain a mixed powder. The mixed powder is dry-pressed at 40 MPa, and then subjected to cold isostatic pressing at 150 MPa for 5 min to obtain a green body. The green body is placed in a high-temperature muffle furnace and sintered in air atmosphere. The heating program was set as follows: from room temperature to 600℃, heating rate 1.5℃ / min, holding at 600℃ for 1.5h for debinding; from 600℃ to 1200℃, heating rate 8℃ / min; from 1200℃ to 1580℃, heating rate 3℃ / min; holding at 1580℃ for 3h; then cooling to room temperature at 4℃ / min; the surface of the sintered ceramic sheet was ground and polished to make the surface roughness Ra≤0.6μm, ultrasonically cleaned and dried.
[0076] The ceramic material prepared in Comparative Example 2 exhibited extensive glassy phase segregation after sintering, with a bulk density of only 3.42 g / cm³. 3 The grains grew abnormally, and the initial insulation strength was only 28.9 kV / mm, which could not meet the requirements for high-voltage use. It broke down directly at 300 kV and could not undergo aging repair testing. This indicates that glass powder without a shell will melt prematurely and react excessively with the matrix during sintering, severely damaging the density and insulation properties of the ceramic, thus proving the necessity of a core-shell structure.
[0077] Comparative Example 3: This comparative example uses the same formulation and process as Example 1, but the amount of conductive triggering nanoparticles (SiC) added is increased to 3.0%. Specifically, microcapsules are prepared according to step 1 of Example 1, using 1000g of 96% alumina powder, 60g of microcapsules, 30g of SiC nanoparticles, and 2.5g of MgO, 10g of TiO2, and 3g of Y2O3 as sintering aids. The above powders are mixed and ball-milled, dried, and sieved to obtain a mixed powder. The mixed powder is then dry-pressed at 40MPa, followed by cold isostatic pressing at 150MPa for 5 minutes to obtain a green body. The green body is then placed in a high-temperature muffle furnace and sintered in air. The heating program was set as follows: from room temperature to 600℃, heating rate 1.5℃ / min, holding at 600℃ for 1.5h for debinding; from 600℃ to 1200℃, heating rate 8℃ / min; from 1200℃ to 1580℃, heating rate 3℃ / min; holding at 1580℃ for 3h; then cooling to room temperature at 4℃ / min; the surface of the sintered ceramic sheet was ground and polished to make the surface roughness Ra≤0.6μm, ultrasonically cleaned and dried.
[0078] The ceramic material prepared in Comparative Example 3 showed localized conductive areas on its surface after sintering, with a bulk density of 3.58 g / cm³. 3 The initial insulation strength decreased to 36.2 kV / mm. After 50 hours of electrical aging at 300 kV, the insulation strength decreased to 22.5 kV / mm. After repair by holding at 120°C for 2 hours, it only recovered to 28.6 kV / mm, and the sample showed obvious localized heating marks. This indicates that excessive conductive triggering nanoparticles can form a conductive network, reduce the initial insulation performance, and affect the repair effect, thus proving that the addition range of 0.2% to 1.5% in this invention is an optimized critical range.
[0079] Table 1. Comparison of insulation strength performance before and after repair in Examples 1-5 and Comparative Examples 1-3.
[0080] Based on the above embodiments and comparative examples, the present invention has the following significant advantages: the initial insulation strength of the ceramic materials prepared in Examples 1-5 all reached above 46kV / mm. After aging at 300~350kV high voltage for 50h, and after a simple heat treatment at 100~150℃ for 1.5~2h, the insulation strength can be restored to more than 93% of the initial value after one repair. Combined with the comparative examples, this fully demonstrates the necessity and superiority of the synergistic design of core-shell structured microcapsules, conductive triggering nanoparticles and alumina matrix in the present invention.
[0081] This application provides a high-voltage insulating ceramic material for high-energy X-ray tubes. The ceramic material comprises an alumina ceramic matrix, microcapsules, and conductive triggering nanoparticles. The alumina ceramic matrix contains 96%–99% alumina by mass. The microcapsules are dispersed at the grain boundaries of the alumina ceramic matrix and have a core-shell structure. The core layer material is a low-melting-point glass with a softening temperature of 500℃–750℃, and the volume resistivity of the low-melting-point glass below 800℃ is ≥1×10⁻⁶. 8 Ω·cm, room temperature volume resistivity ≥1×10 12 The conductive triggering nanoparticles, with a mass fraction of Ω·cm, are attached to the surface of the microcapsule or dispersed at the grain boundaries to form localized conductive channels at the crack tip, generating Joule heating to trigger microcapsule repair. Based on a 100% mass fraction of the alumina ceramic matrix, the mass fraction of the conductive triggering nanoparticles is 0.2%~1.5%. Under normal service conditions, the microcapsule shell remains intact, and the conductive triggering nanoparticles are dispersed as isolated particles, not forming a continuous conductive network, thus not reducing the initial insulation strength of the ceramic material. When microcracks are generated in the ceramic matrix due to partial discharge or electrical treeing, the crack tip is accompanied by a strong localized electric field concentration and micro-discharge phenomenon. The conductive triggering nanoparticles form localized conductive channels at the crack tip. When the micro-discharge current flows through these conductive channels, Joule heating is generated, causing the temperature of the micro-region around the crack to rapidly rise above the softening point of the core glass, triggering the microcapsule to rupture and release molten glass. Under capillary force, the molten glass rapidly fills the microcrack, and after cooling, forms a dense, high-resistivity glass body, "welding" the crack to restore insulation performance. Meanwhile, since each microcapsule works independently, each repair only consumes a small number of microcapsules in the cracked area, while other unbroken microcapsules remain intact. When new microcracks appear in the material again, the repair process can be repeated, achieving multiple self-repairs. This solves the problem that high-voltage insulating ceramic materials cannot perform in-situ multiple self-repairs of microcracks generated during service while maintaining their initial insulation performance. This application also provides a method for preparing the above-mentioned ceramic material.
[0082] Similar parts between the embodiments provided in this invention can be referred to mutually. The specific embodiments provided above are merely examples under the overall concept of this invention and do not constitute a limitation on the scope of protection of this application. For those skilled in the art, any other embodiments extended from the solution of this invention without creative effort are within the scope of protection of this invention.
Claims
1. A high-voltage insulating ceramic material for high-energy ray tubes, characterized in that, The ceramic material comprises an alumina ceramic matrix, microcapsules, and conductive triggering nanoparticles. The alumina ceramic matrix contains 96%–99% alumina by mass. The microcapsules are dispersed at the grain boundaries of the alumina ceramic matrix and have a core-shell structure. The core layer material is a low-melting-point glass with a softening temperature of 500℃–750℃, and the volume resistivity of the low-melting-point glass below 800℃ is ≥1×10⁻⁶. 8 Ω·cm, room temperature volume resistivity ≥1×10 12 Ω·cm; The conductive triggering nanoparticles are attached to the surface of the microcapsule or dispersed at the grain boundaries to form a local conductive channel at the crack tip, generating Joule heat to trigger microcapsule repair. The mass fraction of the conductive triggering nanoparticles is 0.2%~1.5% based on the mass fraction of the alumina ceramic matrix as 100%.
2. The ceramic material according to claim 1, characterized in that, Based on a mass fraction of 100% for the low-melting-point glass, the low-melting-point glass comprises 30%~40% SiO2, 15%~25% B2O3, 12%~20% BaO, 5%~10% Al2O3, 5%~10% ZnO, and 3%~8% CaO, with the sum of the mass percentages of each component being 100%.
3. The ceramic material according to claim 1, characterized in that, The shell material of the microcapsule is one or more of Al2O3, ZrO2, and SiO2, and the thickness of the shell is 0.2μm to 1μm.
4. The ceramic material according to claim 3, characterized in that, The average particle size of the microcapsules is 2μm~12μm, and the mass ratio of the core material to the shell material is (6~12):
1.
5. The ceramic material according to claim 1, characterized in that, The conductive triggering nanoparticles have a particle size of 20 nm to 150 nm.
6. The ceramic material according to claim 1, characterized in that, The conductive triggering nanoparticles are one or more of SiC, TiN, and aluminum-doped zinc oxide.
7. A method for preparing ceramic materials, characterized in that, The method for preparing the ceramic material according to any one of claims 1 to 6 specifically includes: S1 Preparation of microcapsules: Low melting point glass raw materials are mixed, melted, water-quenched, and ball-milled to obtain low melting point glass powder; the glass powder and shell material precursor are spray-dried or fluidized bed coated to obtain core-shell wet particles, and the shell is densified by heat treatment at 700℃~850℃ to obtain microcapsules. S2 Powder Mixing: The microcapsules, alumina powder, conductive triggering nanoparticles and sintering aid are wet ball-milled and mixed for 12-24 hours, dried and sieved to obtain mixed powder. S3 molding: The mixed powder is dry-pressed into shape, and then subjected to cold isostatic pressing to obtain a ceramic green body; S4 High-temperature sintering: The green body is placed in air or a humid hydrogen atmosphere and sintered at 1450℃~1620℃ for 2~4 hours, with segmented heating rate controlled throughout the sintering process. S5 Post-processing: The sintered ceramic blank is subjected to surface grinding, polishing, cleaning and drying to obtain the finished high-voltage insulating ceramic material.
8. The method according to claim 7, characterized in that, The melting temperature of the low-melting-point glass powder mentioned in S1 is 1200℃~1350℃, and the average particle size of the low-melting-point glass powder after ball milling is 1μm~4μm; the shell material precursor is one of aluminum sol, zirconium sol or silica sol.
9. The method according to claim 7, characterized in that, The sintering aid mentioned in S2 is one or more of MgO, TiO2, CaO, Y2O3, and Cr2O3, and the amount of sintering aid added is 0.25% to 2.5% of the mass of alumina powder.
10. The method according to claim 7, characterized in that, The sintering process control of segmented heating rate described in S4 specifically includes: The temperature is increased from room temperature to 600℃ at a rate of 1℃~2℃ / min, and held for 1~2 hours to allow the adhesive to dissipate; the temperature is increased from 600℃ to 1200℃ at a rate of 5℃~10℃ / min; the temperature is increased from 1200℃ to the sintering temperature at a rate of 2℃~5℃ / min; after holding, the temperature is cooled to room temperature at a rate of 3℃~5℃ / min.